Multi-source remote sensing workflow (PlanetScope and Sentinel-1/2) applied to LULCC analysis (2016–2024) in the SDERM-CGSM Ramsar Site, Colombia - Cristian C. Montes-Chaura; Lina Latorre-Conde; Dayron Quintero-Rodriguez; Brayan Estupiñan-Angarita; José Rodriguez-Bolaños; Jesús Emilio Pinto-Lopera (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Atmospheric Dynamics and Diversity of Alternaria and Fusarium in a Common Wheat (Triticum aestivum L.) Crop in NW Spain - Kenia C. Sánchez Espinosa; Esperanza Duarte-Escalante; María Fernández-González; María del Rocío Reyes-Montes; Francisco Javier Rodríguez-Rajo (Journal of Crop Health, 2026)
This study investigated the diversity of Alternaria and Fusarium species in atmospheric aerosols and plant tissue in a common wheat crop in NW Spain. The relationship between atmospheric fungal spore concentrations and weather conditions was analysed. To this end, non-viable and viable aerobiological monitoring methodologies were combined with isolates from plants showing symptoms of fungal infection. The isolates were identified by morphological characterisation and phylogenetic analysis of the 1‑alpha elongation factor (TEF-1α). Redundancy analysis was used to quantify the weight of delayed energy and water factors on spore dynamics. The global RDA model was significant, explaining 15.8% of the total variance. Alternaria was associated with wind speed and temperature, while Fusarium was linked to precipitation and humidity on the previous day. The coincidence of Alternaria species in the air and on plants was confirmed. However, while a high diversity of Fusarium species was identified in plant tissue, F . oxysporum predominated in the air. These findings underscore the need for future species-specific epidemiological models and the use of monitoring systems that allow for a comprehensive characterisation of the agroecosystem.

Mainstream and fast-track genetic testing in pancreatic cancer patients and its impact on treatment: our experience in a tertiary hospital in Spain - M. Bringas; I. Echavarría; C. Polo; N. Jiménez-Alduán; C. Flores; A. Muñoz; L. Ortega; G. Torres; J. Soto-Alsar; A. Calvo; P. García Alfonso; J. A. Pajares; et al. (Familial Cancer, 2026)

Novel insights into eugenol anaesthesia in poeciliid larvae: Preliminary study of gill histology - María C. Vercellini; Ramiro Rearte; Ana Carranza‐Martín; Matías H. Assandri; Silvina Vargas; Martin M. Montes; Miguel A. Ayala (Journal of Fish Biology, 2026)
The increasing use of fish in research emphasizes the need for effective and safe anaesthetic protocols, particularly for early life stages. Eugenol has been proposed as a promising anaesthetic, yet information regarding its effects on Cnesterodon decemmaculatus larvae remains scarce. This study assessed anaesthesia and recovery times, as well as gill tissue integrity, in larvae exposed to different eugenol concentrations. A randomized controlled trial was conducted using four treatment groups (6, 12.5, 25 and 50 mgL −1 ) and a control group (10 mgL −1 ethanol). Significant differences were observed in both anaesthesia and recovery times across treatments ( p p ≤ 0.02), and filament perimeter was also significantly reduced in all treatments ( p −1 exhibited significantly more necrotic foci than controls ( p −1 , decreased at 12.5 and 25 mgL −1 ( p −1 ( p p ≥ 0.08). However, oedema was higher at 6 mgL −1 than at 12.5 mgL −1 ( p = 0.02), and congestion was lower at 12.5 mgL −1 than 25 mgL −1 ( p = 0.04). Overall, the results indicate that 12.5 mgL −1 eugenol provides effective anaesthesia with minimal histological alterations, representing the optimal concentration for use in C. decemmaculatus larvae.

Revealing the phylogeography of Astyanax lacustris: insights from the São Francisco River clade - Renata S. Farias; Breno H. C. Barros; Bruno C. Nascimento; Leonardo L. Calado; Reginaldo de Carvalho; Martin A. Montes; Maria R. M. Coimbra (Hydrobiologia, 2026)
The genus Astyanax is highly diverse within the family Acestrorhamphidae, and species identification remains challenging due to overlapping morphological, morphometric, meristic, and coloration traits. As a result, several taxa have been considered as species complexes or treated as synonyms. Molecular and cytogenetic approaches are essential for clarifying taxonomic boundaries and assessing potential genetic divergence among Astyanax populations. This study aimed to investigate potential genetic and cytogenetic divergence within A. lacustris from the São Francisco (SF), Northeastern Caatinga and Coastal Drainages (CD), and Upper Paraná (PR) basins. Forty individuals from the Submiddle stretch of the São Francisco River (SMSF) were compared to 102 mitochondrial cytochrome c oxidase subunit I (COI) sequences identified as A. lacustris in the BOLD database from the three ecoregions. The mean K2P divergence between PR and the remaining basins was 3.8%. Both the Bayesian inference tree and the haplotype network revealed a distinct separation between PR samples and the other basins. Cytogenetic analyses also detected differences in karyotype formulas between these groups. Altogether, our results reveal deep genetic and cytogenetic divergence between the Paraná lineage and the São Francisco–Northeastern Caatinga and Coastal Drainages group, highlighting the need for refined taxonomic assessments within this complex.

Effects of apomorphine, spinal rTMS, and BoNT on camptocormia: an exploratory wearable sensor-based analysis in a patient with MSA - D. De Monte; G.M. Squintani; G. Ermanis; F. Lavezzi; S. Flumignan; G. Valiante; B.H. Ercole; E. Belgrado; A. Bernardini; Y. Tereshko; M. Valente; S. Rossi; et al. (Toxicon, 2026)

In vivo evaluation of cisplatin(IV) conjugated to iron oxide adipate/tartrate nanoparticles using Drosophila melanogaster - A. Rodríguez Pescador; C. López Portugués; M. Montes-Bayón; E. Blanco González; L.M. Sierra (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2026)

Effect of ceria surface modification on Au/TiO2 and Au/YSZ catalysts for the preferential oxidation of CO - R. Manzorro; C. Mora-Moreno; J.M. Montes-Monroy; D. Goma-Jiménez; G. Blanco; S. Trasobares; J.J. Calvino; A.B. Hungría; J.A. Pérez-Omil; A. Martínez-Arias; M.A. Cauqui (Fuel, 2026)

Effects of Apomorphine, Spinal rTMS, and BoNT on Camptocormia: An Exploratory Wearable Sensor-Based Analysis in a Patient With MSA - D. De Monte; G. Squintani; F. Lavezzi; S. Flumignan; G. Valiante; B.H. Ercole; G. Ermanis; E. Belgrado; A. Bernardini; Y. Tereshko; M. Valente; S. Rossi; et al. (Toxicon, 2026)

Influence of Posidonia oceanica accumulation on beach morphodynamics: A remote sensing study - S. Terracciano; J. Montes; R. Brunetta; P. Cabrita; P. Ciavola; C. Armaroli (Coastal Engineering, 2026)

Magmatic record of Cretaceous marginal basin termination along the western segment of the Central Cordillera of Colombia - J.S. Jaramillo-Ríos; A. Cardona; C. Bustamante; S. Serna; V. Valencia; S. Zapata; J. P. Zapata-Villada; J. Vanegas; L. Gaviria-Montes; S. Echeverri (International Geology Review, 2026)

Panoramic Transect of the Western Flank of Eastern Cordillera Fold and Thrust Belt, Northern Andes, Colombia - C. Montes; C.A. Rosero; F. Lamus; L.C. Perez-Angel; G. Bayona; J.M. Muñoz (Journal of South American Earth Sciences, 2026)

Prospect of kitchen wastes for biomaterials and biogas production in a biorefinery approach - Rebeca Esteban-Lustres; Kai L. Baltrusch; Javier Seijo; Sheyma Inoubli; María Dolores Torres; Guido Domingo; Candida Vannini; Patricia A. Romero-Jung; Beatriz Piñeiro-Lago; Antonio Pazos; Alexandre González-Novoa; Andrea Rodríguez Montes; et al. (Bioresource Technology Reports, 2026)

Phylogenetic analysis and diversity of the Colombian creole donkey from sequences of the mitochondrial DNA D-loop region - D․Y․ Hernández-Herrera; J․ Cordero-Cerón; S․ Martínez-Rodríguez; D․E Montes-Vergara; J․C․ Rincón (Journal of Equine Veterinary Science, 2026)

First detection of Babesia spp. in Amblyomma mixtum from Veracruz, Mexico - Pamela Aguilar-Meraz; Sokani Sánchez-Montes; Ana C. Montes de Oca-Aguilar; Kevin J. Olivares-Calles; Estefanía Grostieta; Carlos I. Miranda Caballero; Amalia Cabrera-Núñez; Dora Romero-Salas; Anabel Cruz-Romero; Mariel Aguilar-Domínguez (Tropical Animal Health and Production, 2026)

Stock identification of the striped mullet Mugil incilis (Actinopterygii: Mugilidae) using truss network, morphometric relationships, and probabilistic models in three regions of the Colombian Caribbean. - K.E. Carrillo-Castro; P. del Monte-Luna; C. Cardenas-Uribe; y.H. Castillo-Navarro (Fisheries Research, 2026)

An uncommon large Eocene wood boring from the Antarctic Peninsula: Evidence of a giant teredinid bivalve? - Jorge Villegas-Martín; Leslie M.E. Manríquez; Bruna C. Schneider; Gerson Fauth; Rodrigo do Monte Guerra; Rodrigo S. Horodyski; Karlos G.D. Kochhann (Palaeoworld, 2025)

Evaluation of benzocaine and eugenol as anesthetics and antiparasitic agents in a freshwater fish model - M. C. Vercellini; A. Carranza-Martin; M. M. Montes; M. A. Ayala (Aquaculture International, 2025)

Climatic and Edaphic Drivers of Soil Organic Carbon and Pyrogenic Carbon Stocks Across Elevation and Disturbance Gradients in Colombian Andean Forests - Carmen R. Montes‐Pulido; Michael I. Bird; Lidiany C. da Silva Carvalho; Julieth Serrano; Carlos A. Quesada; Ted R. Feldpausch (Global Change Biology, 2025)
Understanding the drivers of soil organic carbon (SOC) and soil pyrogenic carbon (PyC) variation and their role in natural and managed ecosystems is increasingly important. However, PyC stocks in tropical Andean soils remain understudied. Here, we examined how edaphic and environmental factors affect PyC across elevation and disturbance gradients in 36 plots spanning natural forests and agrosilvopastoral systems in the Colombian Andes. Across the 0–100 cm soil profile, the mean SOC stock in the study region was 433.10 Mg C ha −1 (range: 67.97–1462 Mg C ha −1 ), while the mean PyC stock was 34.13 Mg C ha −1 (range: 2.29–305.70 Mg C ha −1 ), accounting for approximately ~8% of the total SOC. This PyC stock is approximately nine times greater than the Amazon‐wide average. PyC (%) did not vary significantly with disturbance gradients or soil depths. However, both PyC (%) and SOC (%) varied significantly with elevation zonation ( p p p

Confirmation of the presence of Hemotropic Mycoplasma species in working equids from Veracruz, Mexico - Gerardo G. Ballados-González; Anabel Cruz-Romero; José M. Martínez-Hernández; Mariel Aguilar-Domínguez; Rafael F. C. Vieira; Estefania Grostieta; Ingeborg Becker; Sokani Sánchez-Montes (Tropical Animal Health and Production, 2025)

Magnetic fabrics of weakly-deformed mudrocks from the Jaca-Pamplona basin (Pyrenees); new constrains on the sensitivity of magnetic fabrics and the tectonic evolution of the Southern Pyrenees - P. Sierra-Campos; P. Calvín; E. Izquierdo-Llavall; J. I. Pérez-Landazabal; M. Montes; A. Luzón; E. Bellido; E. L. Pueyo; J. C. Larrasoaña (Journal of Iberian Geology, 2025)
The anisotropy of magnetic susceptibility (AMS) is a sensitive marker for studying the spatial and temporal evolution of orogens. In weakly deformed rocks deposited in compressive contexts the AMS signal mostly reflects the preferential alignment and deformation of paramagnetic phyllosilicates during early layer parallel shortening (LPS) related to both near and/or far-field structures. Moreover, localized deformation and post-depositional shearing in the vicinity of thrusts can alter early LPS fabrics. An AMS analysis of 651 samples was conducted along two stratigraphic sections, Izaga and Berdún (2800 m-thick), in the Jaca-Pamplona basin (Southern Pyrenees). The sampled sections record the tectonosedimentary evolution of the basin from the Late Lutetian to the Middle Priabonian. In both sections, the magnetic fabric is controlled by LPS. The lower and upper part of the Izaga section shows triaxial to oblate and oblate ellipsoids, respectively, which are interpreted to indicate a decrease of tectonic activity associated to the Larra thrust system. The Berdún section begins with oblate ellipsoids, which subsequently become triaxial and prolate before returning oblate towards the top of the succession. Ellipsoids in the lower part of the section exhibit an incipient girdle between the minimum and intermediate axes, which signal an undetected thrust, further corroborated, by structural analysis. The remainder of the Berdún section shows a magnetic fabric derived from LPS but it is not possible to associate it to any structure. The uppermost part of the section displays prolate ellipsoids, which we link to enhanced tectonic activity leading to continentalization of the basin.

Combining Cirrus and Aerosol Corrections for Improved Reflectance Retrievals over Turbid Waters from Visible Infrared Imaging Radiometer Suite Data - Bo-Cai Gao; Rong-Rong Li; Marcos J. Montes; Sean C. McCarthy (Oceans, 2025)
The multi-band atmospheric correction algorithms, now referred to as remote sensing reflectance (Rrs) algorithms, have been implemented on a NASA computing facility for global remote sensing of ocean color and atmospheric aerosol parameters from data acquired with several satellite instruments, including the Visible Infrared Imaging Radiometer Suite (VIIRS) on board the Suomi spacecraft platform. These algorithms are based on the 2-band version of the SeaWiFS (Sea-Viewing Wide Field-of-View Sensor) algorithm. The bands centered near 0.75 and 0.865 μm are used for atmospheric corrections. In order to obtain high-quality Rrs values over Case 1 waters (deep clear ocean waters), strict masking criteria are implemented inside these algorithms to mask out thin clouds and very turbid water pixels. As a result, Rrs values are often not retrieved over bright Case 2 waters. Through our analysis of VIIRS data, we have found that spatial features of bright Case 2 waters are observed in VIIRS visible band images contaminated by thin cirrus clouds. In this article, we describe methods of combining cirrus and aerosol corrections to improve spatial coverage in Rrs retrievals over Case 2 waters. One method is to remove cirrus cloud effects using our previously developed operational VIIRS cirrus reflectance algorithm and then to perform atmospheric corrections with our updated version of the spectrum-matching algorithm, which uses shortwave IR (SWIR) bands above 1 μm for retrieving atmospheric aerosol parameters and extrapolates the aerosol parameters to the visible region to retrieve water-leaving reflectances of VIIRS visible bands. Another method is to remove the cirrus effect first and then make empirical atmospheric and sun glint corrections for water-leaving reflectance retrievals. The two methods produce comparable retrieved results, but the second method is about 20 times faster than the spectrum-matching method. We compare our retrieved results with those obtained from the NASA VIIRS Rrs algorithm. We will show that the assumption of zero water-leaving reflectance for the VIIRS band centered at 0.75 μm (M6) over Case 2 waters with the NASA Rrs algorithm can sometimes result in slight underestimates of water-leaving reflectances of visible bands over Case 2 waters, where the M6 band water-leaving reflectances are actually not equal to zero. We will also show conclusively that the assumption of thin cirrus clouds as ‘white’ aerosols during atmospheric correction processes results in overestimates of aerosol optical thicknesses and underestimates of aerosol Ångström coefficients.

Electrochemical degradation of tebuthiuron pesticide using a flow reactor: Insights into the co-generation of oxidants and ecotoxicological risks - Robson S. Souto; Isaac Sánchez-Montes; Géssica O.S. Santos; Paulo J.M. Cordeiro-Junior; Renata Colombo; Mauro C. Santos; Marcos R.V. Lanza (Journal of Environmental Chemical Engineering, 2025)

Ozone injection system based on NETmix technology for quaternary treatment of urban wastewater - Mateus Mestriner Pituco; Paulo H. Marrocos; Sandra Méndez; Rosa Montes; Rosario Rodil; Francisca C. Moreira; Vítor J.P. Vilar (Journal of Environmental Chemical Engineering, 2025)

Non-hyperbolic enzyme kinetics: the case of P-type ATPases - S. E. Faraj; M. R. Montes; R. D. Peluffo; R. M. González-Lebrero; R. C. Rossi (Biophysical Reviews, 2025)

Adaptive thermal comfort models comparison in dry and rainy seasons: A tropical climate case - J.G. Sánchez-Montes; J.J. Flores-Prieto; L.A López-Pérez; C. Ríos-Rojas (Energy and Buildings, 2025)

Assessing organic carbon sequestration in soil aggregates for building high quality carbon stocks in improved grazing lands - Tushar C. Sarker; Anil C. Somenahally; Adrian Romero; Monte Rouquette; Gerald Smith; Girisha Ganjegunte (Agriculture, Ecosystems & Environment, 2025)

Corrigendum to “Hydrothermal extraction of ulvans from Ulva spp.in a biorefinery approach” [Sci. Total Environ 951 (2024) 175654] - Pablo Rodríguez-Iglesias; Kai L. Baltrusch; Beatriz Díaz-Reinoso; Miriam López-Álvarez; Ramón Novoa-Carballal; Pío González; Alexandre González-Novoa; Andrea Rodríguez-Montes; Christian Kennes; María C. Veiga; M. Dolores Torres; Herminia Domínguez (Science of The Total Environment, 2025)

EuPPollNet : A European Database of Plant‐Pollinator Networks - Jose B. Lanuza; Tiffany M. Knight; Nerea Montes‐Perez; Will Glenny; Paola Acuña; Matthias Albrecht; Maddi Artamendi; Isabelle Badenhausser; Joanne M. Bennett; Paolo Biella; Ricardo Bommarco; Andree Cappellari; et al. (Global Ecology and Biogeography, 2025)
Motivation Pollinators play a crucial role in maintaining Earth's terrestrial biodiversity. However, rapid human‐induced environmental changes are compromising the long‐term persistence of plant‐pollinator interactions. Unfortunately, we lack robust, generalisable data capturing how plant‐pollinator communities are structured across space and time. Here, we present the EuPPollNet (European Plant‐Pollinator Networks) database, a fully open European‐level database containing harmonised taxonomic data on plant‐pollinator interactions referenced in both space and time, along with other ecological variables of interest. In addition, we evaluate the taxonomic and sampling coverage of EuPPollNet, and summarise key structural properties in plant‐pollinator networks. We believe EuPPollNet will stimulate research to address data gaps in plant‐pollinator interactions and guide future efforts in conservation planning. Main Types of Variables Included EuPPollNet contains 1,162,109 interactions between plants and pollinators from 1864 distinct networks, which belong to 52 different studies distributed across 23 European countries. Information about sampling methodology, habitat type, biogeographic region and additional taxonomic rank information (i.e. order, family, genus and species) is also provided. Spatial Location and Grain The database contains 1214 different sampling locations from 13 different natural and anthropogenic habitats that fall in 7 different biogeographic regions. All records are geo‐referenced and presented in the World Geodetic System 1984 (WGS84). Time Period and Grain Species interaction data was collected between 2004 and 2021. Major Taxa and Level of Measurement The database contains interaction data at the species level for 94% of the records, including a total of 1411 plant and 2223 pollinator species. The database includes data on 6% of the European species of flowering plants, 34% of bees, 26% of butterflies and 33% of syrphid species at the European level. Software Format The database was built with R and is stored in ‘.rds’ and ‘.csv’ formats. Its construction is fully reproducible and can be accessed at: https://doi.org/10.5281/zenodo.14747448 .

Hemoplasma in melon-headed whale (Peponocephala electra, Gray, 1846), Veracruz, Mexico - Gerardo.G. Ballados-González; Juan Casas-Paul; Maria del Carmen C. Ruiz-Murillo; Graciela I. Bernal-Trejo; Kurt Navarro-Castañeda; Marco D. Perez-Medina; Roberto Ibarra-Laclette; Anabel Cruz-Romero; Arturo Serrano; Celina Naval-Ávila; Miguel A. Lammoglia-Villagómez; Estefanía Grostieta; et al. (Comparative Immunology, Microbiology and Infectious Diseases, 2025)

DES-based leachates containing LCO, NMC or NCA oxides as electrolytes for 2.2 V supercapacitors - Laura González-Aguilera; José Manuel Vicent-Luna; M. Luisa Ferrer; Francisco del Monte; María C. Gutiérrez (Chemical Engineering Journal, 2025)

High removal of PS and PET microplastics from tap water by using Fe2O3 porous microparticles and photothermal irradiation with NIR light - J.M. Sanchez; J. Oliva; C. Gomez-Solis; E. Puentes-Prado; E. Montes; I. Juárez-Ramírez; C.R. Garcia; J. Moreno Palmerin (Chemosphere, 2024)

Hydrothermal extraction of ulvans from Ulva spp. in a biorefinery approach - Pablo Rodríguez-Iglesias; Kai L. Baltrusch; Beatriz Díaz-Reinoso; Miriam López-Álvarez; Ramón Novoa-Carballal; Pío González; Alexandre González-Novoa; Andrea Rodríguez-Montes; Christian Kennes; María C. Veiga; María D. Torres; Herminia Domínguez (Science of The Total Environment, 2024)

Integration of a 3D-printed electrochemical reactor with a tubular membrane photoreactor to promote sulfate-based advanced oxidation processes - Agustina R. de Olivera; Carla S. Santos; Ismael F. Mena; Miguel A. Montiel; Rosa Montes; José B. Quintana; Rosario Rodil; Ana I. Gomes; Francisca C. Moreira; Jan Gäbler; Lothar Schäfer; C. Sáez; et al. (Chemical Engineering Journal, 2024)

Selective electrochemical oxidation of organic compounds in a mass transfer-enhanced electrochemical flow reactor (eNETmix) - Clarissa H. Rosa; Daniela F.S. Morais; Gilber R. Rosa; João H.Z. dos Santos; José Carlos B. Lopes; Madalena M. Dias; Rosa Montes; Rosario Rodil; José Benito Quintana; Gabriel Antonio Cerrón-Calle; Sergi Garcia-Segura; Carlos J. Tavares; et al. (Journal of Environmental Chemical Engineering, 2024)

Recovering connectivity through restoration corridors in a fragmented landscape in the magdalena river’s valley in Colombia - Andrés Montes-Rojas; Nicolás Alejandro José Delgado-Morales; Rafael S. Escucha; Laura C. Siabatto; Andrés Link (Biodiversity and Conservation, 2024)
Forest fragmentation is one of the main drivers of global biodiversity loss leading to the isolation of wildlife populations. This study focuses on understanding the role of restoration corridors as a strategy promoting resilience and viability of mammal and bird populations in a fragmented landscape in Colombia. We installed 98 camera-trap stations − 8497 camera-trap days - in four different land cover categories: (1) forest fragments, (2) natural corridors, (3) stablished corridors and (4) pastures. We evaluated if restoration corridors do promote connectivity for large vertebrates and recover species richness and functional diversity lost in anthropogenically transformed pastures. We used indices of taxonomic and functional diversity and a non-metric multidimensional scaling to evaluate the influence of land cover over mammal and bird communities. Both, species richness and functional diversity have higher values in forests, followed by natural corridors and corridors and lower values in open pastures. Differences in species composition were greater between forests and pastures, and species composition of restoration corridors begins to resemble that of riparian forests and forest fragments. Our results provide initial evidence on the role of restoration corridors as an efficient strategy aimed to recover biodiversity and functional diversity in pervasively fragmented landscapes.

Continuous UV-C/H2O2 and UV-C/Chlorine applied to municipal secondary effluent and nanofiltration retentate: Removal of contaminants of emerging concern, ecotoxicity, and reuse potential - Fernando Rodrigues-Silva; Carla S. Santos; Joaquín A. Marrero; Rosa Montes; José Benito Quintana; Rosario Rodil; Olga C. Nunes; Maria Clara V.M. Starling; Camila C. Amorim; Ana I. Gomes; Vítor J.P. Vilar (Chemosphere, 2024)

Genetic (co)variation for resistance to white spot syndrome virus, acute hepatopancreatic necrosis, and overall pond survival in Litopenaeus vannamei - Reyes López-Ordaz; Alejandra Caballero-Zamora; José M. Yáñez; Leobardo Montoya-Rodríguez; Bruno Gómez-Gil; Sonia A. Soto Rodríguez; Alfonso Martínez Ortega; Juan C. Quintana-Casares; Héctor Castillo-Juárez; Gabriel R. Campos-Montes (Aquaculture International, 2024)

Exceptionally preserved subfossil woods from late Pleistocene volcanic deposits from the Northern Andes of Colombia - D. Aurelia Ayala-Usma; Rafael Lozano-Gutiérrez; Catalina Orejuela; Lina C. Pérez-Ángel; Camilo Montes; Catalina González-Arango (Review of Palaeobotany and Palynology, 2024)

Optimization of methane production from solid tuna waste: Thermal pretreatment and co-digestion - Noela Bermúdez-Penabad; Andrea Rodríguez-Montes; Madalena Alves; Christian Kennes; María C. Veiga (Waste Management, 2024)

Assessment of satellite-derived shorelines automatically extracted from Sentinel-2 imagery using SAET - J.E. Pardo-Pascual; J. Almonacid-Caballer; C. Cabezas-Rabadán; A. Fernández-Sarría; C. Armaroli; P. Ciavola; J. Montes; P.E. Souto-Ceccon; J. Palomar-Vázquez (Coastal Engineering, 2024)

Social-ecological vulnerability to environmental extremes and adaptation pathways in small-scale fisheries of the southern California Current - Fiorenza Micheli; Andrea Saenz-Arroyo; Emilius Aalto; Rodrigo Beas-Luna; Charles A. Boch; Juan Camilo Cardenas; Giulio A. De Leo; Eduardo Diaz; Antonio Espinoza-Montes; Elena Finkbeiner; Jan Freiwald; Stuart Fulton; et al. (Frontiers in Marine Science, 2024)
Coastal ecosystems and human communities are threatened worldwide by climate change, and shocks from social, market and political change. There is an urgent global need to promote resilient food production and livelihoods in the face of these shocks. Small-scale fisheries (SSF) in rural settings can be particularly vulnerable as they frequently lack the resources, rights and infrastructure to respond to shocks originating outside the focal systems. We examined ecological and social outcomes of environmental extremes in a SSF socio-ecological system (SES) by using long-term oceanographic (between 2010-2019) and ecological (2006-2018) data tracking change in a kelp forest ecosystem of Baja California, Mexico, and concurrent documentation of proactive and reactive actions of a fishing community organized in a cooperative. Results indicate a complex landscape of ‘winners’ and ‘losers’ among species and fisheries exposed to unprecedented environmental extremes, including marine heat waves and prolonged hypoxia, and a suite of adaptive actions by the local fishing cooperative, and others in the region, that have helped confront these rapid and drastic changes. Cooperatives have established voluntary marine reserves to promote recovery of affected populations and have invested in diversification of activities enabled by access rights, collective decision-making, and participatory science programs. Results indicate that local actions can support social and ecological resilience in the face of shocks, and that enabling locally-driven adaptation pathways is critical to resilience. This case study highlights the crucial importance of strengthening and supporting rights, governance, capacity, flexibility, learning, and agency for coastal communities to respond to change and sustain their livelihoods and ecosystems in the long run.

Insights into the application of the anodic oxidation process for the removal of per- and polyfluoroalkyl substances (PFAS) in water matrices - Javier López-Vázquez; Carla S. Santos; Rosa Montes; Rosario Rodil; José Benito Quintana; J. Gäbler; L. Schäfer; Francisca C. Moreira; Vítor J.P. Vilar (Chemical Engineering Journal, 2024)

Ocean floor and Barrovian metamorphic events in the Mesozoic Peltetec ophiolitic belt (Ecuador) - F. Villares; I. F. Blanco-Quintero; P. S. Reyes; C. Montes; D. Fuentes; A. Cardona; A. Garcia-Casco (International Geology Review, 2024)

Potential challenges for the restoration of Biscayne Bay (Florida, USA) in the face of climate change effects revealed with predictive models - Vladimir J. Alarcon; Anna C. Linhoss; Christopher R. Kelble; Paul F. Mickle; Alexandra Fine; Enrique Montes (Ocean & Coastal Management, 2024)

Maximum electrodeposition capacity of Pb on a stainless-steel cathode using a galvanostatic regime - J. C. Rojas-Montes; V. J. Martínez-Gómez; J. C. Fuentes-Aceituno; S. Valle-Cervantes; B. P. Gómez-Lozano; L. R. Quiñones-Rosales (International Journal of Environmental Science and Technology, 2023)

Genetic and genomic evaluation for resistance to white spot syndrome virus in post-larvae of Pacific white shrimp (Litopenaeus vannamei) - Gabriel R. Campos-Montes; Baltasar F. Garcia; Thania Medrano-Mendoza; Alejandra Caballero-Zamora; Leobardo Montoya-Rodríguez; Juan C. Quintana-Casares; José M. Yáñez (Aquaculture, 2023)

Ozone membrane contactor for tertiary treatment of urban wastewater: Chemical, microbial and toxicological assessment - Pedro H. Presumido; Sara Ribeirinho-Soares; Rosa Montes; José Benito Quintana; Rosario Rodil; Marta Ribeiro; Teresa Neuparth; Miguel M. Santos; Manuel Feliciano; Olga C. Nunes; Ana I. Gomes; Vítor J.P. Vilar (Science of The Total Environment, 2023)

Total CroFab and Anavip Antivenom Vial Administration in US Rattlesnake Envenomations: 2019–2021 - Nicklaus Brandehoff; Alicia Dalton; Claire Daugherty; Richard C. Dart; Andrew A. Monte (Journal of Medical Toxicology, 2023)
Introduction In 2018, Anavip became available for the treatment of rattlesnake envenomations in the USA. No comparisons between the treatment characteristics of patients have been made since Anavip and CroFab have both been widely available. The objective of this study was to compare the number of antivenom vials administered of CroFab and Anavip during the treatment of rattlesnake envenomations in the USA. Methods This was a secondary analysis of rattlesnake envenomations utilizing the North American Snakebite Registry (NASBR) from 2019 through 2021. Frequencies and proportions were used to summarize demographics and baseline clinical characteristics. The primary outcome was total antivenom vials administered during treatment. Secondary outcomes included the number antivenom administration events, total treatment time, and hospital length of stay. Results Two hundred ninety-one rattlesnake envenomations were analyzed; most occurred in the Western USA ( n = 279, 96 %). One hundred one patients (35%) received only CroFab, 110 (38%) received Anavip only, and 80 (27%) received both products. The median number of vials used was 10 for CroFab, 18 for Anavip, and 20 for both antivenoms. More than one antivenom administration was necessary in thirty-nine (39%) patients that received only CroFab and 76 (69%) patients that received Anavip only. The median total treatment time was 5.5 hours for CroFab, 6.5 for Anavip, and 15.5 hours when both antivenoms were administered. All antivenom groups had a median hospital length of stay of 2 days. Conclusions Rattlesnake envenomated patients in the Western USA treated with CroFab had fewer antivenom vials and fewer antivenom administrations compared to patients treated with Anavip.

Effects of bisphenol F, bisphenol S, and bisphenol AF on cultured human osteoblasts - E. García-Recio; V. J. Costela-Ruiz; L. Melguizo-Rodríguez; J. Ramos-Torrecillas; R. Illescas-Montes; E. De Luna-Bertos; C. Ruiz (Archives of Toxicology, 2023)
Bisphenol A (BPA) analogs, like BPA, could have adverse effects on human health including bone health. The aim was to determine the effect of BPF, BPS and BPAF on the growth and differentiation of cultured human osteoblasts. Osteoblasts primary culture from bone chips harvested during routine dental work and treated with BPF, BPS, or BPAF for 24 h at doses of 10 –5 , 10 –6 , and 10 –7 M. Next, cell proliferation was studied, apoptosis induction, and alkaline phosphatase (ALP) activity. In addition, mineralization was evaluated at 7, 14, and 21 days of cell culture in an osteogenic medium supplemented with BP analog at the studied doses. BPS treatment inhibited proliferation in a dose-dependent manner at all three doses by inducing apoptosis; BPF exerted a significant inhibitory effect on cell proliferation at the highest dose alone by an increase of apoptosis; while BPAF had no effect on proliferation or cell viability. Cell differentiation was adversely affected by treatment with BPA analogs in a dose-dependent, observing a reduction in calcium nodule formation at 21 days. According to the results obtained, these BPA analogs could potentially pose a threat to bone health, depending on their concentration in the organism.

Disasters collide at the intersection of extreme weather and infectious diseases - John M. Drake; Éric Marty; Kamal J. K. Gandhi; Meredith Welch‐Devine; Brian Bledsoe; Marshall Shepherd; Lynne Seymour; Christine C. Fortuin; Cristian Montes (Ecology Letters, 2023)
Natural disasters interact to affect the resilience and prosperity of communities and disproportionately affect low income families and communities of colour. However, due to lack of a common theoretical framework, these are rarely quantified. Observing severe weather events (e.g. hurricanes and tornadoes) and epidemics (e.g. COVID‐19) unfolding in southeastern US communities led us to conjecture that interactions among catastrophic disturbances might be much more considerable than previously recognized. For instance, hurricane evacuations increase human aggregation, a factor that affects the transmission of acute infections like SARS‐CoV‐2. Similarly, weather damage to health infrastructure can reduce a community's ability to provide services to people who are ill. As globalization and human population and movement continue to increase and weather events are becoming more intense, such complex interactions are expected to magnify and significantly impact environmental and human health.

Stand and tree characteristics influence damage severity after a catastrophic hurricane disturbance - Christine C. Fortuin; Cristian R. Montes; James T. Vogt; Kamal J.K. Gandhi (Forest Ecology and Management, 2023)

Mineralization of soil organic matter from equatorial giant podzols submitted to drier pedoclimate: A drainage topochronosequence study - Célia R. Montes; Patricia Merdy; Wilson T.L. da Silva; Débora Ishida; Adopho J. Melfi; Roberta C. Santin; Yves Lucas (CATENA, 2023)

Efficient removal of antibiotics from water via aqueous portlandite carbonation - G. Montes-Hernandez; L. Feugueur; C. Vernier; A.E.S. Van Driessche; F. Renard (Journal of Water Process Engineering, 2023)

Chemosensory representation of first-time oral exposure to ethanol in the orbitofrontal cortex of mice - E. Perrusquia-Hernández; R. D. Andrade-González; S. E. Cifuentes-Mendiola; C. D. Montes-Angeles; K. I. Zepeda-Reyes; Isaac Obed Pérez-Martínez (Experimental Brain Research, 2023)

Genetic diversity, population structure, linkage disequilibrium and GWAS for resistance to WSSV in Pacific white shrimp (Litopenaeus vannamei) using a 50K SNP chip - Thania Medrano-Mendoza; Baltasar F. García; Alejandra Caballero-Zamora; José M. Yáñez; Leobardo Montoya-Rodríguez; Juan C. Quintana-Casares; Marina Durán-Aguilar; Gabriel R. Campos-Montes (Aquaculture, 2023)

Modeling subduction on the kitchen table - J. Delgado; J. López; I. Zárate; C. Montes (Journal of Structural Geology, 2023)

Mercury methylation upon coastal sediment resuspension: a worst-case approach under dark conditions - Christiane N. Monte; Ana Paula C. Rodrigues; Petrus M. A. Galvão; Gabriela C. Pontes; Olaf Malm; Júlio C. Wasserman; Wilson Machado (Environmental Monitoring and Assessment, 2022)

Urban biodiversity: State of the science and future directions - Christine C. Rega-Brodsky; Myla F. J. Aronson; Max R. Piana; Ela-Sita Carpenter; Amy K. Hahs; Adriana Herrera-Montes; Sonja Knapp; D. Johan Kotze; Christopher A. Lepczyk; Marco Moretti; Allyson B. Salisbury; Nicholas S. G. Williams; et al. (Urban Ecosystems, 2022)

The Colombian geochronological database (CGD) - Andres F. Rodriguez-Corcho; Yamirka Rojas-Agramonte; Johana A. Barrera-Gonzalez; Maria P. Marroquin-Gomez; Sarah Bonilla-Correa; David Izquierdo-Camacho; Sofia M. Delgado-Balaguera; David Cartwright-Buitrago; Maria D. Muñoz-Granados; William G. Carantón-Mateus; Alejandro Corrales-García; Andrés F. Laverde-Martinez; et al. (International Geology Review, 2022)

Hydrology influences carbon flux through metabolic pathways in the hypolimnion of a Mediterranean reservoir - J. J. Montes-Pérez; R. Marcé; B. Obrador; T. Conejo-Orosa; J. L. Díez; C. Escot; I. Reyes; E. Moreno-Ostos (Aquatic Sciences, 2022)
Global change is modifying meteorological and hydrological factors that influence the thermal regime of water bodies. These modifications can lead to longer stratification periods with enlarged hypolimnetic anoxic periods, which can promote heterotrophic anaerobic processes and alter reservoir carbon cycling. Here, we quantified aerobic and anaerobic heterotrophic processes (aerobic respiration, denitrification, iron and manganese reduction, sulfate reduction, and methanogenesis) on dissolved inorganic carbon (DIC) production in the hypolimnion of a Mediterranean reservoir (El Gergal, Spain) under two contrasting hydrological conditions: a wet year with heavy direct rainfall and frequent water inputs from upstream reservoirs, and a dry year with scarce rainfall and negligible water inputs. During the wet year, water inputs and rainfall induced low water column thermal stability and earlier turnover. By contrast, thermal stratification was longer and more stable during the dry year. During wet conditions, we observed lower DIC accumulation in the hypolimnion, mainly due to weaker sulfate reduction and methanogenesis. By contrast, longer stratification during the dry year promoted higher hypolimnetic DIC accumulation, resulting from enhanced methanogenesis and sulfate reduction, thus increasing methane emissions and impairing reservoir water quality. Aerobic respiration, denitrification and metal reduction produced a similar amount of DIC in the hypolimnion during the two studied years. All in all, biological and geochemical (calcite dissolution) processes explained most of hypolimnetic DIC accumulation during stratification regardless of the hydrological conditions, but there is still ~ 30% of hypolimnetic DIC production that cannot be explained by the processes contemplated in this study and the assumptions made.

Genetic structure and management of the Neotropical migratory fish Megaleporinus obtusidens on a highly impacted river basin - Karine K. C. Oliveira-Farias; Renata S. Farias; Miguel A. S. Neto; Marília E. de Souza; Leonardo L. Calado; Martin A. Montes; Ana P. S. Lima; Paulino Martinez; Maria R. M. Coimbra (Hydrobiologia, 2022)

A Global Ocean Oxygen Database and Atlas for Assessing and Predicting Deoxygenation and Ocean Health in the Open and Coastal Ocean - Marilaure Grégoire; Véronique Garçon; Hernan Garcia; Denise Breitburg; Kirsten Isensee; Andreas Oschlies; Maciej Telszewski; Alexander Barth; Henry C. Bittig; Jacob Carstensen; Thierry Carval; Fei Chai; et al. (Frontiers in Marine Science, 2021)
In this paper, we outline the need for a coordinated international effort toward the building of an open-access Global Ocean Oxygen Database and ATlas (GO 2 DAT) complying with the FAIR principles (Findable, Accessible, Interoperable, and Reusable). GO 2 DAT will combine data from the coastal and open ocean, as measured by the chemical Winkler titration method or by sensors (e.g., optodes, electrodes) from Eulerian and Lagrangian platforms (e.g., ships, moorings, profiling floats, gliders, ships of opportunities, marine mammals, cabled observatories). GO 2 DAT will further adopt a community-agreed, fully documented metadata format and a consistent quality control (QC) procedure and quality flagging (QF) system. GO 2 DAT will serve to support the development of advanced data analysis and biogeochemical models for improving our mapping, understanding and forecasting capabilities for ocean O 2 changes and deoxygenation trends. It will offer the opportunity to develop quality-controlled data synthesis products with unprecedented spatial (vertical and horizontal) and temporal (sub-seasonal to multi-decadal) resolution. These products will support model assessment, improvement and evaluation as well as the development of climate and ocean health indicators. They will further support the decision-making processes associated with the emerging blue economy, the conservation of marine resources and their associated ecosystem services and the development of management tools required by a diverse community of users (e.g., environmental agencies, aquaculture, and fishing sectors). A better knowledge base of the spatial and temporal variations of marine O 2 will improve our understanding of the ocean O 2 budget, and allow better quantification of the Earth’s carbon and heat budgets. With the ever-increasing need to protect and sustainably manage ocean services, GO 2 DAT will allow scientists to fully harness the increasing volumes of O 2 data already delivered by the expanding global ocean observing system and enable smooth incorporation of much higher quantities of data from autonomous platforms in the open ocean and coastal areas into comprehensive data products in the years to come. This paper aims at engaging the community (e.g., scientists, data managers, policy makers, service users) toward the development of GO 2 DAT within the framework of the UN Global Ocean Oxygen Decade (GOOD) program recently endorsed by IOC-UNESCO. A roadmap toward GO 2 DAT is proposed highlighting the efforts needed (e.g., in terms of human resources).

The Peltetec ophiolitic belt (Ecuador): a window to the tectonic evolution of the Triassic margin of western Gondwana - F. Villares; A. Garcia-Casco; I. F. Blanco-Quintero; C. Montes; P. S. Reyes; A. Cardona (International Geology Review, 2021)

Stratification strength and light climate explain variation in chlorophyll a at the continental scale in a European multilake survey in a heatwave summer - Daphne Donis; Evanthia Mantzouki; Daniel F. McGinnis; Dominic Vachon; Irene Gallego; Hans‐Peter Grossart; Lisette N. de Senerpont Domis; Sven Teurlincx; Laura Seelen; Miquel Lürling; Yvon Verstijnen; Valentini Maliaka; et al. (Limnology and Oceanography, 2021)
To determine the drivers of phytoplankton biomass, we collected standardized morphometric, physical, and biological data in 230 lakes across the Mediterranean, Continental, and Boreal climatic zones of the European continent. Multilinear regression models tested on this snapshot of mostly eutrophic lakes (median total phosphorus [TP] = 0.06 and total nitrogen [TN] = 0.7 mg L −1 ), and its subsets (2 depth types and 3 climatic zones), show that light climate and stratification strength were the most significant explanatory variables for chlorophyll a (Chl a ) variance. TN was a significant predictor for phytoplankton biomass for shallow and continental lakes, while TP never appeared as an explanatory variable, suggesting that under high TP, light, which partially controls stratification strength, becomes limiting for phytoplankton development. Mediterranean lakes were the warmest yet most weakly stratified and had significantly less Chl a than Boreal lakes, where the temperature anomaly from the long‐term average, during a summer heatwave was the highest (+4°C) and showed a significant, exponential relationship with stratification strength. This European survey represents a summer snapshot of phytoplankton biomass and its drivers, and lends support that light and stratification metrics, which are both affected by climate change, are better predictors for phytoplankton biomass in nutrient‐rich lakes than nutrient concentrations and surface temperature.

Establishing the Foundation for the Global Observing System for Marine Life - Erin V. Satterthwaite; Nicholas J. Bax; Patricia Miloslavich; Lavenia Ratnarajah; Gabrielle Canonico; Daniel Dunn; Samantha E. Simmons; Roxanne J. Carini; Karen Evans; Valerie Allain; Ward Appeltans; Sonia Batten; et al. (Frontiers in Marine Science, 2021)
Maintaining healthy, productive ecosystems in the face of pervasive and accelerating human impacts including climate change requires globally coordinated and sustained observations of marine biodiversity. Global coordination is predicated on an understanding of the scope and capacity of existing monitoring programs, and the extent to which they use standardized, interoperable practices for data management. Global coordination also requires identification of gaps in spatial and ecosystem coverage, and how these gaps correspond to management priorities and information needs. We undertook such an assessment by conducting an audit and gap analysis from global databases and structured surveys of experts. Of 371 survey respondents, 203 active, long-term (>5 years) observing programs systematically sampled marine life. These programs spanned about 7% of the ocean surface area, mostly concentrated in coastal regions of the United States, Canada, Europe, and Australia. Seagrasses, mangroves, hard corals, and macroalgae were sampled in 6% of the entire global coastal zone. Two-thirds of all observing programs offered accessible data, but methods and conditions for access were highly variable. Our assessment indicates that the global observing system is largely uncoordinated which results in a failure to deliver critical information required for informed decision-making such as, status and trends, for the conservation and sustainability of marine ecosystems and provision of ecosystem services. Based on our study, we suggest four key steps that can increase the sustainability, connectivity and spatial coverage of biological Essential Ocean Variables in the global ocean: (1) sustaining existing observing programs and encouraging coordination among these; (2) continuing to strive for data strategies that follow FAIR principles (findable, accessible, interoperable, and reusable); (3) utilizing existing ocean observing platforms and enhancing support to expand observing along coasts of developing countries, in deep ocean basins, and near the poles; and (4) targeting capacity building efforts. Following these suggestions could help create a coordinated marine biodiversity observing system enabling ecological forecasting and better planning for a sustainable use of ocean resources.

Using richness of native and non-native aquatic species along a climatic gradient to test the intermediate disturbance hypothesis - Luciano N. Santos; Ana Clara S. Franco; Joice S. de Souza; Igor C. Miyahira; Antonio Jailson S. Rodrigues; Isabela Cristina B. Gonçalves; Natascha Krepsky; Helga A. B. Monte; Clarissa Naveira; Tatiana M. B. Cabrini; Rayane R. S. Abude; Matheus Augusto; et al. (Hydrobiologia, 2021)

The Genomics of Elevated ALT and Adducts in Therapeutic Acetaminophen Treatment: a Pilot Study - Andrew A. Monte; Brandon Sonn; Jessica Saben; Barry H. Rumack; Kate M. Reynolds; Richard C. Dart; Kennon J. Heard (Journal of Medical Toxicology, 2021)

Pyrite Flotation Separation and Encapsulation: A Synchronized Remediation System for Tailings Dams - P. Camero-Hermoza; D. Calla-Choque; J. C. Rojas-Montes; C. Villachica-Leon; J. Villachica-Llamosas (Mine Water and the Environment, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

Contrasting Futures for Australia’s Fisheries Stocks Under IPCC RCP8.5 Emissions – A Multi-Ecosystem Model Approach - Heidi R. Pethybridge; Elizabeth A. Fulton; Alistair J. Hobday; Julia Blanchard; Catherine M. Bulman; Ian R. Butler; William W. L. Cheung; Leo X. C. Dutra; Rebecca Gorton; Trevor Hutton; Richard Matear; Hector Lozano-Montes; et al. (Frontiers in Marine Science, 2020)

Isolation and characterization of 15 new microsatellite markers for the globally endangered Lear’s macaw Anodorhynchus leari - Erica C. Pacífico; Gregorio Sánchez-Montes; Cristina Y. Miyaki; José L. Tella (Molecular Biology Reports, 2020)

Soil rock content influences the maximum seedling emergence depth of a dominant arid zone grass - Monte Masarei; Lachlan C. Astfalck; Andrew L. Guzzomi; David J. Merritt; Todd E. Erickson (Plant and Soil, 2020)

Upregulation of β3-adrenoceptors—a general marker of and protective mechanism against hypoxia? - Massimo Dal Monte; Bronwyn A. Evans; Ebru Arioglu-Inan; Martin C. Michel (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Sorbent Materials Characterization Based on Mechanical or Thermal Pretreated Montmorillonite Modified by Surfactant Loading for Improved Chromium Retention - César Fernández Morantes; Florencia Yarza; María L. Montes; Roberto C. Mercader; Gustavo Curutchet; Rosa M. Torres Sánchez (Water, Air, & Soil Pollution, 2020)

Multidisciplinary Observing in the World Ocean’s Oxygen Minimum Zone Regions: From Climate to Fish — The VOICE Initiative - Véronique Garçon; Johannes Karstensen; Artur Palacz; Maciej Telszewski; Tony Aparco Lara; Denise Breitburg; Francisco Chavez; Paulo Coelho; Marcela Cornejo-D’Ottone; Carmen Santos; Björn Fiedler; Natalya D. Gallo; et al. (Frontiers in Marine Science, 2019)

Verbal Memory and Learning in Schoolchildren Exposed to Manganese in Mexico - Z. García-Chimalpopoca; D. Hernández-Bonilla; M. Cortez-Lugo; C. Escamilla-Núñez; A. Schilmann; H. Riojas-Rodríguez; S. Rodríguez-Dozal; S. Montes; L. A. Tristán-López; M. Catalán-Vázquez; C. Rios (Neurotoxicity Research, 2019)

Global Observational Needs and Resources for Marine Biodiversity - Gabrielle Canonico; Pier Luigi Buttigieg; Enrique Montes; Frank E. Muller-Karger; Carol Stepien; Dawn Wright; Abigail Benson; Brian Helmuth; Mark Costello; Isabel Sousa-Pinto; Hanieh Saeedi; Jan Newton; et al. (Frontiers in Marine Science, 2019)

Toward a Coordinated Global Observing System for Seagrasses and Marine Macroalgae - J. Emmett Duffy; Lisandro Benedetti-Cecchi; Joaquin Trinanes; Frank E. Muller-Karger; Rohani Ambo-Rappe; Christoffer Boström; Alejandro H. Buschmann; Jarrett Byrnes; Robert G. Coles; Joel Creed; Leanne C. Cullen-Unsworth; Guillermo Diaz-Pulido; et al. (Frontiers in Marine Science, 2019)

Genetic and geographic variation in growth of Balanites aegyptiaca in Niger: comparing results from provenance/progeny tests in the nursery and field - John C. Weber; Carmen Sotelo Montes; Idrissa Soumana; Boukary Ousmane Diallo; Tougiani Abasse; Mahamane Larwanou; André Babou Bationo (New Forests, 2019)

Mitral Valve Prosthesis Design Affects Hemodynamic Stasis and Shear In The Dilated Left Ventricle - Vi Vu; Lorenzo Rossini; Ricardo Montes; Josue Campos; Juyeun Moon; Pablo Martinez-Legazpi; Javier Bermejo; Juan C. del Álamo; Karen May-Newman (Annals of Biomedical Engineering, 2019)

Adenovirus 5 produces obesity and adverse metabolic, morphological, and functional changes in the long term in animals fed a balanced diet or a high-fat diet: a study on hamsters - Daniel A. Montes-Galindo; Ana C. Espiritu-Mojarro; Valery Melnikov; Norma A. Moy-López; Alejandro D. Soriano-Hernandez; Hector R. Galvan-Salazar; Jorge Guzman-Muñiz; Jose Guzman-Esquivel; Margarita L. Martinez-Fierro; Iram P. Rodriguez-Sanchez; Brenda Paz-Michel; Sergio A. Zaizar-Fregoso; et al. (Archives of Virology, 2019)

Phylogeography of a widespread lizard complex reflects patterns of both geographic and ecological isolation - Levi N. Gray; Anthony J. Barley; Steven Poe; Robert C. Thomson; Adrián Nieto‐Montes de Oca; Ian J. Wang (Molecular Ecology, 2019)
A primary challenge for modern phylogeography is understanding how ecology and geography, both contemporary and historical, shape the spatial distribution and evolutionary histories of species. Phylogeographic patterns are the result of many factors, including geology, climate, habitat, colonization history and lineage‐specific constraints. Assessing the relative influences of these factors is difficult because few species, regions and environments are sampled in enough detail to compare competing hypotheses rigorously and because a particular phylogeographic pattern can potentially result from different evolutionary scenarios. The silky anoles ( Anolis sericeus complex) of Central America and Mexico are abundant and found in all types of lowland terrestrial habitat, offering an excellent opportunity to test the relative influences of the factors affecting diversification. Here, we performed a range‐wide statistical phylogeographic analysis on restriction site‐associated DNA (RAD) markers from silky anoles and compared the phylogeographic patterns we recovered to historical and contemporary environmental and topographic data. We constructed niche models to compare niche overlap between sister lineages and conducted coalescent simulations to characterize how the major lineages of silky anoles have diverged. Our results revealed that the mode of divergence for major lineage diversification events was geographic isolation, resulting in ecological divergence between lineages, followed by secondary contact. Moreover, comparisons of parapatric sister lineages suggest that ecological niche divergence contributed to isolation by environment in this system, reflecting the natural history differences among populations in divergent environments.

Similar photosynthetic response to elevated carbon dioxide concentration in species with different phloem loading strategies - Kristen A. Bishop; Pauline Lemonnier; Jennifer C. Quebedeaux; Christopher M. Montes; Andrew D. B. Leakey; Elizabeth A. Ainsworth (Photosynthesis Research, 2018)

Inflammatory and Anti-inflammatory Responses Co-exist Inside Lung Granuloma of Fatal Cases of Coccidioidomycosis: A Pilot Report - Heidi G. Rodriguez-Ramirez; Adolfo Soto-Dominguez; Gloria M. González; Oralia Barboza-Quintana; Mario C. Salinas-Carmona; Luis A. Ceceñas-Falcon; Roberto Montes-de-Oca-Luna; Alma Y. Arce-Mendoza; Adrian G. Rosas-Taraco (Mycopathologia, 2018)

Variation in growth, wood density and carbon concentration in five tree and shrub species in Niger - John C. Weber; Carmen Sotelo Montes; Tougiani Abasse; Carlos R. Sanquetta; Dimas A. Silva; Sandra Mayer; Graciela I. B. Muñiz; Rosilei A. Garcia (New Forests, 2018)

Involvement of reactive oxygen species in the oleoylethanolamide effects and its pyrazonilic analogue in melanoma cells - Priscila Antiqueira-Santos; Daiane S. dos Santos; Carolina R. L. Hack; Alex Fabiani C. Flores; Marcelo G. Montes D’Oca; Luciana A. Piovesan; Luiz Eduardo M. Nery; Ana Paula S. Votto (Medicinal Chemistry Research, 2017)

Identification of pathogenic fungi and preliminary screening for resistance in Jatropha curcas L. germplasm - Lissette C. Hernández-Cubero; Peter Ampofo; Juan M. Montes; Ralf T. Voegele (European Journal of Plant Pathology, 2017)

Net Heterotrophy in the Amazon Continental Shelf Changes Rapidly to a Sink of CO2 in the Outer Amazon Plume - Nathalie Lefèvre; Manuel Flores Montes; Felipe L. Gaspar; Carlos Rocha; Shan Jiang; Moacyr C. De Araújo; J. Severino Pino Ibánhez (Frontiers in Marine Science, 2017)

NESSCA Validation and Responsiveness of Several Rating Scales in Spinocerebellar Ataxia Type 2 - Thais L. Monte; Estela R. Reckziegel; Marina C. Augustin; Amanda S. P. Silva; Lucas D. Locks-Coelho; Orlando Barsottini; José L. Pedroso; Fernando R. Vargas; Maria-Luiza Saraiva-Pereira; Vanessa Bielefeldt Leotti; Laura Bannach Jardim (The Cerebellum, 2017)

Variation in growth, wood stiffness and density, and correlations between growth and wood stiffness and density in five tree and shrub species in the Sahelian and Sudanian ecozones of Mali - Carmen Sotelo Montes; John C. Weber; Rosilei A. Garcia; Dimas A. Silva; Graciela I. B. Muñiz (Trees, 2017)

Descriptions of the Immature Stages of Lutzomyia (Tricholateralis) cruciata (Coquillett) (Diptera: Psychodidae, Phlebotominae) - A C Montes de Oca-Aguilar; E A Rebollar-Téllez; P M Piermarini; S Ibáñez-Bernal (Neotropical Entomology, 2017)

Contributions of Dryland Forest (Caatinga) to Species Composition, Richness and Diversity of Drosophilidae - G F Oliveira; C Rohde; A C L Garcia; M A Montes; V L S Valente (Neotropical Entomology, 2016)

Population growth of three mirid predatory bugs feeding on eggs and larvae of Tuta absoluta on tomato - Diego B. Silva; Vanda H. P. Bueno; Flavio C. Montes; Joop C. van Lenteren (BioControl, 2016)

Nebulized Delivery of the MAPKAP Kinase 2 Peptide Inhibitor MMI-0100 Protects Against Ischemia-Induced Systolic Dysfunction - David I. Brown; Brian C. Cooley; Megan T. Quintana; Cynthia Lander; Monte S. Willis (International Journal of Peptide Research and Therapeutics, 2016)

Identification of a Hemagglutinin from Gallibacterium anatis - J. F. Montes-García; S. Vaca; C. Vazquez-Cruz; E. Soriano-Vargas; F. Aguilar-Romero; P. J. Blackall; E. Negrete-Abascal (Current Microbiology, 2016)

Changes in Cd and Zn bioavailability upon an experimental resuspension of highly contaminated coastal sediments from a tropical estuary - Christiane N. Monte; Ana P. C. Rodrigues; Renato C. Cordeiro; Aline S. Freire; Ricardo E. Santelli; W. Machado (Sustainable Water Resources Management, 2015)

Genetic variation and clines in growth and survival of Prosopis africana from Burkina Faso and Niger: comparing results and conclusions from a nursery test and a long-term field test in Niger - John C. Weber; Carmen Sotelo Montes; Antoine Kalinganire; Tougiani Abasse; Mahamane Larwanou (Euphytica, 2015)

Phenotypic and Molecular Characterization of Leptospira interrogans Isolated from Canis familiaris in Southern Brazil - Sérgio Jorge; Leonardo G. Monte; Natasha R. De Oliveira; Thais F. Collares; Bárbara C. Roloff; Charles K. Gomes; Daiane D. Hartwig; Odir A. Dellagostin; Cláudia P. Hartleben (Current Microbiology, 2015)

Removal of heavy metals and arsenic from aqueous solution using textile wastes from denim industry - D. I. Mendoza-Castillo; C. K. Rojas-Mayorga; I. P. García-Martínez; M. A. Pérez-Cruz; V. Hernández-Montoya; A. Bonilla-Petriciolet; M. A. Montes-Morán (International Journal of Environmental Science and Technology, 2015)

Large multiethnic Candidate Gene Study for C-reactive protein levels: identification of a novel association at CD36 in African Americans - Jaclyn Ellis; Ethan M. Lange; Jin Li; Josee Dupuis; Jens Baumert; Jeremy D. Walston; Brendan J. Keating; Peter Durda; Ervin R. Fox; Cameron D. Palmer; Yan A. Meng; Taylor Young; et al. (Human Genetics, 2014)

Growth and fuelwood properties of five tree and shrub species in the Sahelian and Sudanian ecozones of Mali: relationships with mean annual rainfall and geographical coordinates - Carmen Sotelo Montes; John C. Weber; Dimas A. Silva; Clarice Andrade; Graciela I. B. Muñiz; Rosilei A. Garcia; Antoine Kalinganire (New Forests, 2014)

Glutamate Excitotoxicity Activates the MAPK/ERK Signaling Pathway and Induces the Survival of Rat Hippocampal Neurons In Vivo - Daniel Ortuño-Sahagún; Raúl Montes González; Ester Verdaguer; Verónica Chaparro Huerta; Blanca M. Torres-Mendoza; Lourdes Lemus; Martha Catalina Rivera-Cervantes; A. Camins; C. Beas Zárate (Journal of Molecular Neuroscience, 2014)

Physical activity, sex steroid, and growth factor concentrations in pre- and post-menopausal women: a cross-sectional study within the EPIC cohort - S. Rinaldi; R. Kaaks; C. M. Friedenreich; T. J. Key; R. Travis; C. Biessy; N. Slimani; K. Overvad; J. N. Østergaard; A. Tjønneland; A. Olsen; S. Mesrine; et al. (Cancer Causes & Control, 2014)

Lifestyle, dietary factors, and antibody levels to oral bacteria in cancer-free participants of a European cohort study - Dominique S. Michaud; Jacques Izard; Zachary Rubin; Ingegerd Johansson; Elisabete Weiderpass; Anne Tjønneland; Anja Olsen; Kim Overvad; Marie Christine Boutron-Ruault; Françoise Clavel-Chapelon; Laure Dossus; Rudolf Kaaks; et al. (Cancer Causes & Control, 2013)

Morphological aspects and histological effects of the attachment organ of Parabrachiella sp. (Copepoda: Lernaeopodidae) on the grey mullet, Mugil liza Valenciennes - S E Plaul; M M Montes; C G Barbeito; S R Martorelli (Journal of Fish Diseases, 2013)
The genus Parabrachiella Wilson, 1915 (Lernaeopodidae) is represented by copepods that are highly adapted to a parasitic way of life. In Argentina, only P . insidiosa var. lageniformis Heller, 1865, P . chevreuxii Van Beneden, 1891 and P . spinicephala Ringuelet, 1945 have been cited, but none of these have been reported on mugilids. Recently, other species of this genus were found attached to the nasal cavities of juvenile grey mullets, Mugil liza Valenciennes, from Samborombón bay, Buenos Aires province. In this study, the prevalence and mean intensity of the Parabrachiella sp. on grey mullet is investigated. In addition, the damage the parasite imposes on its hosts is examined through evaluation of histological sections and immunostaining for proliferative cell nuclear antigen ( PCNA ). The morphology of the parasite's bulla is described from light and scanning electron micrographs.

Wuschel overexpression promotes somatic embryogenesis and induces organogenesis in cotton (Gossypium hirsutum L.) tissues cultured in vitro - O. Bouchabké-Coussa; M. Obellianne; D. Linderme; E. Montes; A. Maia-Grondard; F. Vilaine; C. Pannetier (Plant Cell Reports, 2013)

Concentration of ascorbic acid and antioxidant response in early life stages of Engraulis ringens and zooplankton during the spawning seasons of 2006–2009 off central Chile - M. C. Krautz; L. R. Castro; M. González; A. Llanos-Rivera; I. Montes; H. González; R. R. González; J. C. Vera (Marine Biology, 2013)

Surface atmospheric circulation patterns and associated minimum temperatures in the Maipo and Casablanca valleys, central Chile - Carlo Montes; Ricardo C. Muñoz; Jorge F. Perez-Quezada (Theoretical and Applied Climatology, 2013)

Effect of 17ß-estradiol on zinc content of hippocampal mossy fibers in ovariectomized adult rats - E. Padilla-Gómez; V. Beltrán-Campos; S. Montes; A. Díaz-Ruíz; G. L. Quirarte; C. Ríos; S. Diaz-Cintra (BioMetals, 2012)

Recovery of ponderosa pine ecosystem carbon and water fluxes from thinning and stand‐replacing fire - Sabina Dore; Mario Montes‐Helu; Stephen C. Hart; Bruce A. Hungate; George W. Koch; John B. Moon; Alex J. Finkral; Thomas E. Kolb (Global Change Biology, 2012)
Carbon uptake by forests is a major sink in the global carbon cycle, helping buffer the rising concentration of CO 2 in the atmosphere, yet the potential for future carbon uptake by forests is uncertain. Climate warming and drought can reduce forest carbon uptake by reducing photosynthesis, increasing respiration, and by increasing the frequency and intensity of wildfires, leading to large releases of stored carbon. Five years of eddy covariance measurements in a ponderosa pine ( Pinus ponderosa )‐dominated ecosystem in northern Arizona showed that an intense wildfire that converted forest into sparse grassland shifted site carbon balance from sink to source for at least 15 years after burning. In contrast, recovery of carbon sink strength after thinning, a management practice used to reduce the likelihood of intense wildfires, was rapid. Comparisons between an undisturbed‐control site and an experimentally thinned site showed that thinning reduced carbon sink strength only for the first two posttreatment years. In the third and fourth posttreatment years, annual carbon sink strength of the thinned site was higher than the undisturbed site because thinning reduced aridity and drought limitation to carbon uptake. As a result, annual maximum gross primary production occurred when temperature was 3 °C higher at the thinned site compared with the undisturbed site. The severe fire consistently reduced annual evapotranspiration (range of 12–30%), whereas effects of thinning were smaller and transient, and could not be detected in the fourth year after thinning. Our results show large and persistent effects of intense fire and minor and short‐lived effects of thinning on southwestern ponderosa pine ecosystem carbon and water exchanges.

Characterizing 25 years of change in the area, distribution, and carbon stock of Mediterranean pines in Central Spain - Cristina Gómez; Michael A. Wulder; Joanne C. White; Fernando Montes; José A. Delgado (International Journal of Remote Sensing, 2012)

Evaporation from Heterogeneous and Sparse Canopies: On the Formulations Related to Multi-Source Representations - J. P. Lhomme; C. Montes; F. Jacob; L. Prévot (Boundary-Layer Meteorology, 2012)

Prediagnostic concentrations of plasma genistein and prostate cancer risk in 1,605 men with prostate cancer and 1,697 matched control participants in EPIC - Ruth C. Travis; Naomi E. Allen; Paul N. Appleby; Alison Price; Rudolf Kaaks; Jenny Chang-Claude; Heiner Boeing; Krasimira Aleksandrova; Anne Tjønneland; Nina Føns Johnsen; Kim Overvad; J. Ramón Quirós; et al. (Cancer Causes & Control, 2012)

Molecular detection of the airborne entomopathogen fungus Metarhizium acridum using specific oligonucleotides - C. Calderón-Ezquerro; I. Santiago-López; C. Guerrero-Guerra; M. R. Reyes-Montes; M. E. Calderón-Segura; C. Toriello (Aerobiologia, 2012)

Epidemiological and molecular analysis of Streptococcus pyogenes isolates causing invasive disease in Spain (1998–2009): comparison with non-invasive isolates - M. Montes; C. Ardanuy; E. Tamayo; A. Domènech; J. Liñares; E. Pérez-Trallero (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Growth of pruned eucalypt clone in an agroforestry system in southeastern Brazil - Ivan C. I. Fontan; Geraldo G. Reis; Maria G. F. Reis; Helio G. Leite; Marco A. Monte; Diêgo C. Ramos; Felippe C. Souza (Agroforestry Systems, 2011)

Building collaboration and learning in integrated catchment management: the importance of social process and multiple engagement approaches - W Allen; A Fenemor; M Kilvington; G Harmsworth; RG Young; N Deans; C Horn; C Phillips; O Montes de Oca; J Ataria; R Smith (New Zealand Journal of Marine and Freshwater Research, 2011)
Success at integrated catchment management (ICM) requires the ongoing participation of different stakeholders in an adaptive and learning‐based management process. However, this can be difficult to achieve in practice because many initiatives fail to address the underlying social process aspects required. We review emerging lessons around how to engage stakeholders in ways that support social learning. We focus on the experience of an ICM research programme based in the Motueka catchment in New Zealand and provide a simple framework for distinguishing a range of conversations across different communities of practice. We highlight the need to use multiple engagement approaches to address different constituent needs and opportunities, and to encourage the informal conversations that spring up around these. We then illustrate the range of platforms for dialogue and learning that were used in the programme during 10 years of ICM research. Finally, a number of lessons are described from across the programme to guide research leaders and managers seeking to improve collaboration in other integrated science, management and policy initiatives.

Integrating Environmental and Socio-Economic Indicators of a Linked Catchment–Coastal System Using Variable Environmental Intensity - John R. Dymond; Tim J. A. Davie; Andrew D. Fenemor; Jagath C. Ekanayake; Ben R. Knight; Anthony O. Cole; Oscar Montes de Oca Munguia; Will J. Allen; Roger G. Young; Les R. Basher; Marc Dresser; Chris J. Batstone (Environmental Management, 2010)

Evaluation of methods for estimating soil carbon dioxide efflux across a gradient of forest disturbance - B. W. SULLIVAN; S. DORE; T. E. KOLB; S. C. HART; M. C. MONTES‐HELU (Global Change Biology, 2010)
Better understanding of variation in soil carbon dioxide (CO 2 ) efflux caused by measurement techniques is needed, especially over gradients of site disturbance, to accurately estimate the global carbon cycle. We present soil CO 2 efflux data from a gradient of disturbance to ponderosa pine ( Pinus ponderosa C. Lawson var. scopulorum Engelm.) forests in northern Arizona, USA that were obtained using four different techniques: vented static chambers, a Licor 6400‐09, and soil CO 2 diffusion profiles using two different models (Moldrup, Millington–Quirk) to estimate soil gas diffusivity. We also compared soil CO 2 efflux measured by the Moldrup and Millington–Quirk diffusion profile methods to nighttime total ecosystem respiration (TER) data from an eddy covariance tower. We addressed four questions: (1) Does the use of a given method to measure soil CO 2 efflux bias results across a disturbance gradient? (2) Does the magnitude of difference between observed and modeled estimates of soil CO 2 differ between methods and across sites? (3) What is the spatial variability of each method at each site? (4) Which method is closest to the estimate of TER measured by the eddy covariance tower? Although soil CO 2 efflux varied significantly among methods the differences were consistent among sites. Measured and modeled total growing season fluxes were generally higher for the Licor 6400‐09 and Millington–Quirk diffusion gradient methods compared with static chamber and the Moldrup diffusion gradient methods. A power analysis showed that the larger static chamber was the most efficient method at sampling spatial variation in soil CO 2 efflux. Nighttime measurements of soil CO 2 efflux from the Moldrup diffusion gradient method were most strongly related to nighttime TER assessed with eddy covariance. The use of a single, well‐implemented method to measure soil CO 2 efflux is unlikely to create bias in comparisons across a gradient of forest disturbance.

Retrieval of Substrate Bearing Strength from Hyperspectral Imagery during the Virginia Coast Reserve (VCR’07) Multi-Sensor Campaign - Charles M. Bachmann; C. Reid Nichols; Marcos J. Montes; Rong-Rong Li; Patrick Woodward; Robert A. Fusina; Wei Chen; Vimal Mishra; Wonkook Kim; James Monty; Kevin Mcilhany; Ken Kessler; et al. (Marine Geodesy, 2010)

Alveolar recruiting maneuver in dogs under general anesthesia: effects on alveolar ventilation, gas exchange, and respiratory mechanics - F. Staffieri; V. De Monte; C. De Marzo; F. Scrascia; A. Crovace (Veterinary Research Communications, 2010)

Phenotypic correlations and site effects in a Peruvian landrace of peach palm (Bactris gasipaes Kunth) - J. P. Cornelius; J. C. Weber; C. Sotelo-Montes; L. J. Ugarte-Guerra (Euphytica, 2010)

Effects of climate‐driven primary production change on marine food webs: implications for fisheries and conservation - C. J. BROWN; E. A. FULTON; A. J. HOBDAY; R. J. MATEAR; H. P. POSSINGHAM; C. BULMAN; V. CHRISTENSEN; R. E. FORREST; P. C. GEHRKE; N. A. GRIBBLE; S. P. GRIFFITHS; H. LOZANO‐MONTES; et al. (Global Change Biology, 2010)
Climate change is altering the rate and distribution of primary production in the world's oceans. Primary production is critical to maintaining biodiversity and supporting fishery catches, but predicting the response of populations to primary production change is complicated by predation and competition interactions. We simulated the effects of change in primary production on diverse marine ecosystems across a wide latitudinal range in Australia using the marine food web model Ecosim. We link models of primary production of lower trophic levels (phytoplankton and benthic producers) under climate change with Ecosim to predict changes in fishery catch, fishery value, biomass of animals of conservation interest, and indicators of community composition. Under a plausible climate change scenario, primary production will increase around Australia and generally this benefits fisheries catch and value and leads to increased biomass of threatened marine animals such as turtles and sharks. However, community composition is not strongly affected. Sensitivity analyses indicate overall positive linear responses of functional groups to primary production change. Responses are robust to the ecosystem type and the complexity of the model used. However, model formulations with more complex predation and competition interactions can reverse the expected responses for some species, resulting in catch declines for some fished species and localized declines of turtle and marine mammal populations under primary productivity increases. We conclude that climate‐driven primary production change needs to be considered by marine ecosystem managers and more specifically, that production increases can simultaneously benefit fisheries and conservation. Greater focus on incorporating predation and competition interactions into models will significantly improve the ability to identify species and industries most at risk from climate change.

Bathymetry Retrieval from Hyperspectral Imagery in the Very Shallow Water Limit: A Case Study from the 2007 Virginia Coast Reserve (VCR'07) Multi-Sensor Campaign - Charles M. Bachmann; Marcos J. Montes; Robert A. Fusina; Christopher Parrish; Jon Sellars; Alan Weidemann; Wesley Goode; C. Reid Nichols; Patrick Woodward; Kevin McIlhany; Victoria Hill; Richard Zimmerman; et al. (Marine Geodesy, 2010)

Correlations and clines in tree growth and wood density of Balanites aegyptiaca (L.) Delile provenances in Niger - John C. Weber; Carmen Sotelo Montes (New Forests, 2010)

Determination of mycotoxin concentration by ELISA and near-infrared spectroscopy in Fusarium-inoculated maize - C. Bolduan; J. Montes; B. Dhillon; V. Mirdita; A. Melchinger (Cereal Research Communications, 2009)

Soil CO 2 flux and photoautotrophic community composition in high‐elevation, ‘barren’ soil - Kristen R. Freeman; Monte Y. Pescador; Sasha C. Reed; Elizabeth K. Costello; Michael S. Robeson; Steven K. Schmidt (Environmental Microbiology, 2009)
Summary Soil‐dominated ecosystems, with little or no plant cover (i.e. deserts, polar regions, high‐elevation areas and zones of glacial retreat), are often described as ‘barren’, despite their potential to host photoautotrophic microbial communities. In high‐elevation, subnival zone soil (i.e. elevations higher than the zone of continuous vegetation), the structure and function of these photoautotrophic microbial communities remains essentially unknown. We measured soil CO 2 flux at three sites (above 3600 m) and used molecular techniques to determine the composition and distribution of soil photoautotrophs in the Colorado Front Range. Soil CO 2 flux data from 2002 and 2007 indicate that light‐driven CO 2 uptake occurred on most dates. A diverse community of Cyanobacteria , Chloroflexi and eukaryotic algae was present in the top 2 cm of the soil, whereas these clades were nearly absent in deeper soils (2–4 cm). Cyanobacterial communities were composed of lineages most closely related to Microcoleus vaginatus and Phormidium murrayi , eukaryotic photoautotrophs were dominated by green algae, and three novel clades of Chloroflexi were also abundant in the surface soil. During the light hours of the 2007 snow‐free measurement period, CO 2 uptake was conservatively estimated to be 23.7 g C m −2 season −1 . Our study reveals that photoautotrophic microbial communities play an important role in the biogeochemical cycling of subnival zone soil.

Long‐term impact of a stand‐replacing fire on ecosystem CO 2 exchange of a ponderosa pine forest - S. DORE; T. E. KOLB; M. MONTES‐HELU; B. W. SULLIVAN; W. D. WINSLOW; S. C. HART; J. P. KAYE; G. W. KOCH; B. A. HUNGATE (Global Change Biology, 2008)
Ponderosa pine ( Pinus ponderosa ) forests of the southwestern United States are a mosaic of stands where undisturbed forests are carbon sinks, and stands recovering from wildfires may be sources of carbon to the atmosphere for decades after the fire. However, the relative magnitude of these sinks and sources has never been directly measured in this region, limiting our understanding of the role of fire in regional and US carbon budgets. We used the eddy covariance technique to measure the CO 2 exchange of two forest sites, one burned by fire in 1996, and an unburned forest. The fire was a high‐intensity stand‐replacing burn that killed all trees. Ten years after the fire, the burned site was still a source of CO 2 to the atmosphere [109±6 (SEM) g C m −2 yr −1 ], whereas the unburned site was a sink (−164±23 g C m −2 yr −1 ). The fire reduced total carbon storage and shifted ecosystem carbon allocation from the forest floor and living biomass to necromass. Annual ecosystem respiration was lower at the burned site (480±5 g C m −2 yr −1 ) than at the unburned site (710±54 g C m −2 yr −1 ), but the difference in gross primary production was even larger (372±13 g C m −2 yr −1 at the burned site and 858±37 g C m −2 yr −1 at the unburned site). Water availability controlled carbon flux in the warm season at both sites, and the burned site was a source of carbon in all months, even during the summer, when wet and warm conditions favored respiration more than photosynthesis. Our study shows that carbon losses following stand‐replacing fires in ponderosa pine forests can persist for decades due to slow recovery of the gross primary production. Because fire exclusion is becoming increasingly difficult in dry western forests, a large US forest carbon sink could shift to a decadal‐scale carbon source.

Geographic variation in tree growth and wood density of Guazuma crinita Mart. in the Peruvian Amazon - John C. Weber; Carmen Sotelo Montes (New Forests, 2008)

Intraspecific diversity within avocado field isolates of Rosellinia necatrix from south-east Spain - M. López; D. Ruano-Rosa; C. J. López-Herrera; E. Monte; R. Hermosa (European Journal of Plant Pathology, 2008)

Origins and genetic conservation of tropical trees in agroforestry systems: a case study from the Peruvian Amazon - Ian K. Dawson; Peter M. Hollingsworth; Jeff J. Doyle; Steve Kresovich; John C. Weber; Carmen Sotelo Montes; Terrence D. Pennington; R. Toby Pennington (Conservation Genetics, 2008)

Effect of Sub-lethal Concentrations of Endosulfan on Phagocytic and Hematological Parameters in Nile Tilapia (Oreochromis niloticus) - M. I. Girón-Pérez; M. Montes-López; L. A. García-Ramírez; C. A. Romero-Bañuelos; M. L. Robledo-Marenco (Bulletin of Environmental Contamination and Toxicology, 2008)

Genetic variation in wood color and its correlations with tree growth and wood density of Calycophyllum spruceanum at an early age in the Peruvian Amazon - Carmen Sotelo Montes; Roger E. Hernández; Jean Beaulieu; John C. Weber (New Forests, 2007)

Urinary Excretion of Zinc and Metabolic Control of Patients with Diabetes Type 2 - Dilina do Nascimento Marreiro; Maria do Perpetuo Socorro C. Martins; Simone Sady Ribeiro de Sousa; Véritas Ibiapina; Silva Torres; Liliane Viana Pires; Nadir do Nascimento Nogueira; José Maria Correia Lima; Semíramis Jamil Hadad do Monte (Biological Trace Element Research, 2007)

The Calibration Kit Spectral Fluorescence Standards—A Simple and Certified Tool for the Standardization of the Spectral Characteristics of Fluorescence Instruments - D. Pfeifer; K. Hoffmann; A. Hoffmann; C. Monte; U. Resch-Genger (Journal of Fluorescence, 2006)

Maintenance of Squash (Cucurbita spp.) Landrace Diversity by Farmers' Activities in Mexico - Salvador Montes-Hernández; Laura C. Merrick; Luis E. Eguiarte (Genetic Resources and Crop Evolution, 2005)

Traceability in Fluorometry: Part II. Spectral Fluorescence Standards - U. Resch-Genger; D. Pfeifer; C. Monte; W. Pilz; A. Hoffmann; M. Spieles; K. Rurack; J. Hollandt; D. Taubert; B. Schönenberger; P. Nording (Journal of Fluorescence, 2005)

Traceability in Fluorometry—Part I: Physical Standards - J. Hollandt; R. D. Taubert; J. Seidel; U. Resch-Genger; A. Gugg-Helminger; D. Pfeifer; C. Monte; W. Pilz (Journal of Fluorescence, 2005)

SHORT COMMUNICATION: Do farmers reduce genetic diversity when they domesticate tropical trees? A case study from Amazonia - P. M. HOLLINGSWORTH; I. K. DAWSON; W. P. GOODALL‐COPESTAKE; J. E. RICHARDSON; J. C. WEBER; C. SOTELO MONTES; R. T. PENNINGTON (Molecular Ecology, 2005)
Agroforestry ecosystems may be an important resource for conservation and sustainable use of tropical trees, but little is known of the genetic diversity they contain. Inga edulis , a widespread indigenous fruit tree in South America, is used as a model to assess the maintenance of genetic diversity in five planted vs. five natural stands in the Peruvian Amazon. Analysis of five SSR (simple sequence repeat) loci indicated lower allelic variation in planted stands [mean corrected allelic richness 31.3 (planted) and 39.3 (natural), P = 0.009]. Concerns regarding genetic erosion in planted Amazonian tree stands appear valid, although allelic variation on‐farm is still relatively high.

Ecosystem metabolism in a Mediterranean shallow lake (Laguna de Santa Olalla, Doñana National Park, SW Spain) - Ana I. López-Archilla; Salvador Mollá; María C. Coleto; María C. Guerrero; Carlos Montes (Wetlands, 2004)

Pneumocystis jiroveci isolates with dihydropteroate synthase mutations in patients with chronic bronchitis - E. Caldern; C. de la Horra; F.J. Medrano; A. Lpez-Surez; M.A. Montes-Cano; N. Respaldiza; J. Elvira-Gonzlez; J. Martn-Juan; A. Bascuana; J.M. Varela (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

Genetic differentiation and trade among populations of peach palm (Bactris gasipaes Kunth) in the Peruvian Amazon—implications for genetic resource management - A. Adin; J. C. Weber; C. Sotelo Montes; H. Vidaurre; B. Vosman; M. J. M. Smulders (Theoretical and Applied Genetics, 2004)

Dissemination of emm 28 Erythromycin-, Clindamycin- and Bacitracin-Resistant Streptococcus pyogenes in Spain - B. Orden; J. M. Marimon; E. Perez-Trallero; C. Garcia; M. Montes (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

Water Characterization and Seasonal Heavy Metal Distribution in the Odiel River (Huelva, Spain) by Means of Principal Component Analysis - C. Montes-Botella; M. D. Tenorio (Archives of Environmental Contamination and Toxicology, 2003)

Mineralization of 14C-labelled maize in alkaline saline soils - M.L. Luna-Guido; J. Vega-Estrada; A. Ponce-Mendoza; H. Hernandez-Hernandez; M.-C. Montes-Horcasitas; M. Vaca-Mier; L. Dendooven (Plant and Soil, 2003)

Identification of two homologous antigenic peptides derived from L1 HPV-16 and 18 proteins specific for the HLA-B*3901 allele - A. Monroy-García; B. Weiss-Steider; J. Hernández-Montes; V. F. Ortiz-Navarrete; A. Bañuelos-Pánuco; A. Acosta-Araujo; A. Díaz-Quiñón; C. M. López-Graniel; G. Herbert; J. Granados; C. de Leo; R. M. Silva-López; et al. (Archives of Virology, 2002)

Pepper yellow mosaic virus, a new potyvirus in sweetpepper, Capsicum annuum - A. K. Inoue-Nagata; M. E. N. Fonseca; R. O. Resende; L. S. Boiteux; D. C. Monte; A. N. Dusi; A. C. de ávila; R. A. A. van der Vlugt (Archives of Virology, 2002)

Strategies for genetic conservation of trees in the Peruvian Amazon - Gregory A. O'Neill; Ian Dawson; Carmen Sotelo-Montes; Luigi Guarino; Manuel Guariguata; Dean Current; John C. Weber (Biodiversity and Conservation, 2001)

Abstracts of presentations on selected topics at the XIVth international plant protection congress (IPPC) July 25–30, 1999 - R. Hull; H. A. Kuiper; Maryvon Y. Noordam; Marjorie A. Hoy; Jenny S. Cory; A. C. Fereres; P. Gonzalez; F. Meins; Y. Elkind; Benedicte Charrier; P. Meyer; M. Metzlaff; et al. (Phytoparasitica, 1999)

Genetic variation of Calycophyllum spruceanum in the Peruvian Amazon Basin, revealed by amplified fragment length polymorphism (AFLP) analysis - J. R. RUSSELL; J. C. WEBER; A. BOOTH; W. POWELL; C. SOTELO‐MONTES† and I. K. DAWSON (Molecular Ecology, 1999)
An understanding of the level, structure and origin of genetic variation within and among populations of tropical trees is essential for devising optimum management strategies for their sustainable utilization and conservation. Here, amplified fragment length polymorphism (AFLP) analysis was used to partition genetic variation within and among nine populations of the predominantly riverine tree, Calycophyllum spruceanum , sampled across a wide geographical range along river tributaries of the Peruvian Amazon Basin. Analysis of molecular variance ( AMOVA ) employed 65 AFLP markers and revealed most variation among individuals within populations (91%), although variation among populations was highly significant ( P AMOVA indicated a degree of structuring among populations based on geographical proximity, although clustering did not depend on geographical distance alone. No firm evidence was obtained for unidirectional seed dispersal by water playing an important role in determining genetic structure over the geographical range sampled. Implications of data for optimising genetic management of the species are discussed and areas for further study identified.

Presence and organization of an osmotic stress response domain in wild Triticeae species - J. V. Monte; C. Casanova; C. Soler (Theoretical and Applied Genetics, 1998)

Sediment features, primary producers and food web structure in two shallow temporary Lakes (Monegros, Spain) - P. Alcorlo; P. Diaz; J. Lacalle; A. Baltanás; M. Florín; M. C. Guerrero; C. Montes (Water, Air, & Soil Pollution, 1997)

Sediment Features, Primary Producers and Food Web Structure in Two Shallow Temporary Lakes (Monegros, Spain) - P. Alcorlo; P. Díaz; J. Lacalle; A. Baltanás; M Florín; M.C. Guerrero; C. Montes (Water, Air, & Soil Pollution, 1997)

Caratterizzazione aerosporologica del comprensorio di imola in due diverse sedi di rilevamento - V. Cocchi; A. Dal Monte; E. De Benedictis; C. Avellini (Aerobiologia, 1987)